Comparison of Conservative Interventions for Proximal Hamstring Tendinopathy: A Systematic Review and Recommendations for Rehabilitation - Pilar Dizon; Michael Jeanfavre; Gretchen Leff; Rachel Norton (MDPI AG, 2023)
Knowledge of muscular forces and adaptations with hamstring-specific exercises can optimize exercise prescription and tendon remodeling; however, studies investigating the effectiveness of the current conservative management of proximal hamstring tendinopathy (PHT) and outcomes are lacking. The purpose of this review is to provide insights into the efficacy of conservative therapeutic interventions in the management of PHT. In January 2022, databases including PubMed, Web of Science, CINAHL, and Embase were searched for studies assessing the effectiveness of conservative intervention compared with that of a placebo or combination of treatments on functional outcomes and pain. Studies that performed conservative management (exercise therapy and/or physical therapy modalities) in adults 18-65 years were included. Studies that performed surgical interventions or whose subjects had complete hamstring rupture/avulsion greater than a 2 cm displacement were excluded. A total of 13 studies were included: five studies compared exercise interventions, while eight studies investigated a multimodal approach of either shockwave therapy and exercise or a hybrid model incorporating exercise, shockwave therapy, and other modalities, such as ultrasound, trigger point needling, or instrument-assisted soft tissue mobilization. This review supports the notion that the conservative management of PHT may best be optimized through a multimodal approach incorporating a combination of tendon-specific loading at an increased length, lumbopelvic stabilization exercises, and extracorporeal shockwave therapy. With regard to hamstring-specific exercise selection, PHT may be optimally managed by including a progressive loading program at combined angles of the hip flexion at 110 degrees and the knee flexion between 45 and 90 degrees.